A study of the role of the FOXP2 and CNTNAP2 genes in persistent developmental stuttering - Han, Tae-Un; Park, John; Domingues, Carlos F. [UNESP]; Moretti-Ferreira, Danilo [UNESP]; Paris, Emily; Sainz, Eduardo; Gutierrez, Joanne; Drayna, Dennis (Elsevier B.V., 2014)
A number of speech disorders including stuttering have been shown to have important genetic contributions, as indicated by high heritability estimates from twin and other studies. We studied the potential contribution to stuttering from variants in the FOXP2 gene, which have previously been associated with developmental verbal dyspraxia, and from variants in the CNTNAP2 gene, which have been associated with specific language impairment (SLI). DNA sequence analysis of these two genes in a group of 602 unrelated cases, all with familial persistent developmental stuttering, revealed no excess of potentially deleterious coding sequence variants in the cases compared to a matched group of 487 well characterized neurologically normal controls. This was compared to the distribution of variants in the GNPTAB, GNPTG, and NAGPA genes which have previously been associated with persistent stuttering. Using an expanded subject data set, we again found that NAGPA showed significantly different mutation frequencies in North Americans of European descent (p = 0.0091) and a significant difference existed in the mutation frequency of GNPTAB in Brazilians (p = 0.00050). No significant differences in mutation frequency in the FOXP2 and CNTNAP2 genes were observed between cases and controls. To examine the pattern of expression of these five genes in the human brain, real time quantitative reverse transcription PCR was performed on RNA purified from 27 different human brain regions. The expression patterns of FOXP2 and CNTNAP2 were generally different from those of GNPTAB, GNPTG and NAPGA in terms of relatively lower expression in the cerebellum. This study provides an improved estimate of the contribution of mutations in GNPTAB, GNPTG and NAGPA to persistent stuttering, and suggests that variants in FOXP2 and CNTNAP2 are not involved in the genesis of familial persistent stuttering. This, together with the different brain expression patterns of GNPTAB, GNPTG, and NAGPA compared to that of FOXP2 and CNTNAP2, suggests that the genetic neuropathological origins of stuttering differ from those of verbal dyspraxia and SLI. Published by Elsevier Inc.
Keywords: Stuttering; Genetics; FOXP2; CNTNAP2; Gene expression; Human brain